Influencing Factors on Patient Contentment: Digitalization's Moderating Role in East Java's Health Office - Sari, Ervita Indra; Yunus, Eddy; Riyadi, Slamet (PT. Riset Press International, 2024)
This research aims to analyze the role of service quality on patient satisfaction in the East Java Provincial Health Service. The study involved 400 patients at the Outpatient Health Center within the East Java Provincial Health Service. The results showed that Organizational Management had a negative and insignificant effect on patient satisfaction, while Work Culture had a negative and insignificant effect. The physical work environment had a positive and significant effect on patient satisfaction, while Service Quality had a positive and insignificant effect. System digitalization moderated service quality, influencing patient satisfaction. Organizational Management had a negative and insignificant effect on patient satisfaction, while Work Culture had a negative and significant effect. The study highlights the importance of quality health services in achieving patient satisfaction, as it is a level of patient feeling that arises from the performance of the health service they receive. The study also highlights the role of the physical work environment in influencing patient satisfaction through service quality. Overall, the study highlights the importance of addressing the factors that influence patient satisfaction in the East Java Provincial Health Service.